FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DISPEPSIA PADA PASIEN RAWAT JALAN DI KLINIK PRATAMA AISYIYAH TELADAN SATU KOTA MEDAN TAHUN 2022 - FITRIA, NURUL; BATUBARA, HEPPY JELITA SARI (LP2MTBM MAKARIOZ, 2024)
Dyspepsia is a condition where the suffere experiences symptomps in the form of pain or discomfort in the pit of the stomach, nausea, bloating, belching, feeling full quickly and the stomach feels full. Dyspepsia can attack al levels of society from all levels of age and gender, but dyspepsia more often attacks the productive age, because at the production the level of busyness is higher and the lifestyle that pays less attention to health and stress is easy to occur. to determine the factors that influence the incidence of dyspepsia in outpatients at the Pratama Aisyiyah Teladan clinic Medan city in 2022. This type of research is analytical with a cross sectional approarch with Accidental Sampling technique with a sample of 60 aoutpatients who visited the Pratama Aisyiyah Teladan Satu clinic Medan city. This research was conducted on 5 February to 20 April 2022 with univariat and bivariate analysis with chi square test.From 60 respondents mostly experienced functional dyspepsia as many as 41 respondents (68,3%), eating patterns in the good category were 33 respondents (55%) and experienced stress in the mild category as many as 22 respondents (36,7%) with p value for diet is 0,006 and stress is 0,002. There us an effect of diet and stress on the incidence of dyspepsia ini outpatients at the Pratama Aisyiyah Teladan Satu clinic Medan city and how to dealt with stress so as to prevents dyspepsia.